UPAYA MENINGKATKAN KINERJA KARYAWAN MELALUI MOTIVASI KERJA DI BANDAR UDARA TUNGGUL WULUNG CILACAP - Togap Rama Manullang; Sri Sutarwati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Work motivation plays an important role in employee performance, including, the Tunggul Wulung Cilacap Airport must provide very appropriate work motivation for employees to improve the quality of employee performance. The study aims to determine the efforts made by the Tunggul Wulung Cilacap Airport in improving employee performance through providing work motivation and obstacles faced by the Tunggul Wulung Cilacap Airport in motivating employee work. The research uses qualitative descriptive research methods, data sources are obtained: primary and secondary data. Data collection techniques use observation, interviews, and documentation. Researchers use data analysis techniques: reduction, display, and drawing conclusions. The results showed that the efforts made by the Tunggul Wulung Cilacap Airport in improving employee performance through providing work motivation which includes providing a sense of comfort for employees at work, carrying out work supervision activities, providing complete facilities, conducting license training, rewarding outstanding employees. The obstacles faced by the Tunggul Wulung Cilacap Airport in motivating employee work are giving gifts that must be transferred with overtime pay and new employees do not yet have a license or certificate must attend license training.